The Influence of Internal Auditing on Effective Corporate Governance in the Banking Sector in Oman - Zaroug Osman Bilal; Omar Igbal Twafik; Anaam Khamis Bakhit (European Scientific Journal, ESJ, 2018)
This research aims to examine the influence of internal audit on effective corporate governance in commercial banks listed on Muscat Securities Market (MSM) in Oman. A questionnaire was used to collect data and was distributed to the 100 top senior level officials and internal audit department of the commercial banks. The regression model that was used in this study was five dependent variables: internal audit independence; proficiency and due professional care; nature of work; quality assurance and improvement program; and managing the internal audit activity. The finding of the research establishes a significant positive relationship between internal audit and effective corporate governance. Variables internal audit independence, proficiency and due professional care, and nature of work were significantly associated with corporate governance. For quality assurance and improvement program and managing the internal audit activity, their influence on corporate governance is not statistically significant.